Revealing Hidden Messages Behind Building Designs - Ayub Muktiono (Jurnal Info Sains : Informatika dan Sains, 2023)
Building design is often considered a form of art that reflects certain values, culture, or messages that the architect or builder wants to convey. The aim of this research is to explore the meaning and messages that may be contained in building design elements, such as shape, color, texture and spatial arrangement. In this research, the method used is a qualitative descriptive method. The results of this research reveal that behind building designs there are hidden messages that reflect the values, culture and ideas of the architect or designer. The building design process not only involves aesthetic and functional considerations, but also integrates philosophical or abstract messages through elements such as shape, color, and structural placement. In addition, in response to increasing concern for the environment, building design also explores sustainability aspects by considering the use of environmentally friendly materials and energy efficiency. These findings show that building design not only encapsulates architectural art and techniques, but also becomes a visual expression of the messages and values that the designers want to convey.